Relationships between low serum vitamin D levels and HBV “a” determinant mutations in chronic hepatitis B patients - Huijuan Zhu; Xingxiang Liu; Yi Ding; Hui Zhou; Yiying Wang; Zhiwei Zhou; Xinxin Li; Zengli Zhang; Chen Dong (Journal of Infection in Developing Countries)
Introduction: Vitamin D is significantly associated with virus replication in chronic hepatitis B virus (HBV) infection. However, the relationship between low serum vitamin D levels and HBV “a” determinant mutations remains unknown. Methodology: A total of 133 chronically HBV-infected, treatment-naive patients were randomly selected in the present study. Serum vitamin D levels were measured by using liquid chromatography-mass spectrometry. The HBV “a” determinant was amplified, sequenced, and analyzed by nested polymerase chain reaction (PCR). Results: Among 133 patients, 36, 88, and 9 patients had vitamin D deficiency (25(OH)D < 14 ng/mL), vitamin D insufficiency (25(OH)D ≥ 14 and < 30 ng/mL), and normal vitamin D serum levels ((25(OH)D ≥ 30 ng/mL), respectively. As results showed, 36 [11 genotype B HBVs (HBV/B) and 25 genotype C HBVs (HBV/C)] were isolated from the vitamin D-deficient group, 88 (48 HBV/B and 40 HBV/C) from the vitamin D-insufficient group, and 4 HBV/C strains from the normal serum-vitamin D group. Compared to the HBV/B infected patients with vitamin D insufficiency, higher rates of amino acid mutation within “a” determinant were detected in HBV/B-infected, vitamin D-deficient patients. Moreover, the change frequency of M133 was 27.27% in HBV/B infected patients with vitamin D deficiency, which was significantly higher than those in the vitamin D-insufficient group (p = 0.040). Conclusions: Vitamin D deficiency is significantly associated with genotype B HBV “a” determinant mutations.